PERAN ORANGTUA DALAM MENGAWASI ANAK DALAM MENGAKSES MEDIA INTERNET UNTUK MEWUJUDKAN PERLINDUNGAN HAK ANAK - Hariyadi, Hariyadi; Arliman S, Laurensius (Kopertis Wilayah X, 2018)
Children as part of citizens, they have the same rights as other citizens, which must be protected and respected by every citizen and State. Family is the first education in shaping a child's personality. The way of parenting and habits that are often done will be reflected in the child's personality. Rapid technological developments have the potential to make it difficult for people, especially children, to distinguish the real world virtual world. On this matter, this article wishes to discuss: 1) how are the conditions and behavior of children in Indonesia at this time? 2) how is the role of parents in supervising children in the use of internet media to realize the protection of children's rights, 3) and realize sustainable child protection. This study uses normative juridical research with a legislative approach. The current behavior conditions of children in Indonesia according to the latest data, at least 30 million children in Indonesia are internet users, and digital media is currently the main choice of communication channels they use, and many are misdirected in using the internet. When the use of social media and digital media is growing rapidly among young people, parental support and digital media integration in education are still lagging behind. So it's time to catch up with 9 recommendations. Sustainable child protection is the ideal of child protection laws, therefore child protection that is sustainable in accessing internet media should also be monitored.